UNIVERSITY INSTRUCTORS’ REFLECTIONS ON THEIR FIRST ONLINE TEACHING EXPERIENCES - Dianne Conrad (Online Learning, 2019)
Moving from traditional face-to-face teaching to teaching online can be a precarious process for instructors. In this qualitative study, I interviewed instructors who were engaged in online teaching, for the first time, in a graduate program at a Canadian university. All instructors had some postsecondary face-to-face teaching experience. In-depth interviews with the instructors showed that they had very little knowledge of the new medium they were entering and relied heavily on their face-to-face experiences and their own pedagogy. Instructors’ reflections on their performances centered largely on their roles as deliverers of content. They revealed very little awareness of issues of collaborative learning, of learners’ social presence, or of the role of community in online learning environments.